Immunological Aspects of Approved MS Therapeutics - Rommer, Paulus S.; Milo, Ron; Han, May H.; Satyanarayan, Sammita; Sellner, Johann; Hauer, Larissa; Illes, Zsolt; Warnke, Clemens; Laurent, Sarah; Weber, Martin S.; Zhang, Yinan; Stuve, Olaf (Frontiers in Immunology, 2019)
Multiple sclerosis (MS) is the most common neurological immune-mediated disease leading to disability in young adults. The disease’s course is unpredictable, and over time, neurological disabilities accumulate. Interferon beta-1b was the first drug to be approved in the 1990s for relapsing-remitting MS to modulate the disease’s course. Over the past two decades, the disease’s treatment landscape has changed tremendously. Currently, more than a dozen drugs representing 10 substances with different mechanisms of action have been approved (interferon beta preparations, glatiramer acetate, fingolimod, siponimod, mitoxantrone, teriflunomide, dimethyl fumarate, cladribine, alemtuzumab, ocrelizumab, and natalizumab). Ocrelizumab was also the first medication to be approved for primary progressive MS. This review’s objective is to highlight mechanisms of actions and their effects on the immunopathogenesis of MS. Each agent’s clinical development and potential side effects are also discussed.